Parts-per-quadrillion level gas molecule detection: CO-LITES sensing - Haiyue Sun; Shunda Qiao; Ying He; Xiaorong Sun; Yufei Ma (Light: Science & Applications)
Abstract Highly sensitive gas detection plays a crucial role in advanced scientific and technological fields. This paper presents a parts-per-quadrillion (ppq) level ultra-highly sensitive light-induced thermoelectric spectroscopy (LITES) sensor for the first time. The artificial fish swarm algorithm auto-designed multi-pass cell (MPC) with double helix pattern, and the polymer modified round-head quartz tuning fork (QTF) with low-resonant frequency (f 0) were adopted to improve the gas absorption and QTF’s detection ability. The obtained MPC, with a long optical path length (OPL) of 25.8 m and a small volume of 165.8 ml, is beneficial for increasing gas absorption while keeping the sensor compact. The novel QTF was structurally optimized to obtain low f 0 (~9.5 kHz) and modified by polydimethylsiloxane (PDMS) to reduce heat diffusion and enhance vibration amplitude. A strong absorption line of carbon monoxide (CO) located in the mid-infrared region (4.59 μm) was chosen as the target line. The signal-to-noise ratio (SNR) of CO-LITES sensor based on the novel QTF was improved by 10.59 times, reaching the highest level when compared to the commercial QTF. The corresponding minimum detection limit (MDL) was calculated to be 23 ppt. When the integration time of the sensor system was increased to 500 s, the MDL could be improved to 920.7 ppq. Compared to the reported spectroscopy techniques for CO gas detection, the LITES sensor in this study offers an excellent result in terms of detection sensitivity.